Implementation of Transdisciplinary Approaches in Islamic Education to Face Contemporary Global Challenges - Hanif, Abdullah; Wahyudin, Wawan; Sholahuddin, Sholahuddin (Eduprof : Islamic Education Journal, 2025)
This research aims to explore the application of a transdisciplinary approach in Islamic education, with a focus on its integration with contemporary global challenges, such as social, environmental, and technological issues. This study uses a qualitative method with a literature study approach. Data is collected from a variety of secondary sources, such as books, journal articles, and official documents. Data analysis was carried out thematically to find patterns and relationships between transdisciplinary approaches and Islamic education. The focus of the research is the theoretical exploration of transdisciplinary education in the Islamic context. The findings show that the transdisciplinary approach at Sakinah Circle successfully integrates various disciplines such as science, mathematics, history, and language with Qur'anic values. Each theme taught, such as "Water" and "Samawat", provides a holistic learning experience, combining scientific, spiritual, and ethical dimensions. This approach prepares students to face contemporary challenges by fostering intellectual and spiritual development simultaneously. This research highlights the important role of a transdisciplinary approach in modernizing Islamic education to confront global issues such as environmental sustainability and social inequality. The study also demonstrates the need for institutional support in implementing this approach, as well as suggesting that transdisciplinary learning can enhance critical thinking skills, creativity, and collaboration in the context of Islamic education. This research makes an original contribution by linking the transdisciplinary approach to Islamic education, emphasizing its potential in bridging the gap between traditional religious teachings and the demands of the 21st century. This research offers a new perspective on how Islamic education can evolve to face global challenges while maintaining its core values.